Development of an automatic self balancing control system for a tree climbing robot - Shokripour, Hamed; Wan Ismail, Wan Ishak; Karimi, Zahra Moez (Academic Journals, 2011)
The purpose of this project was to design, fabricate and test a self balancing control system for a four wheeled climbing robot. A HM-RF transparent wireless data link module was used for transferring the data between the remote control and robot. A programmed microcontroller ATmega16 was used to generate an appropriate signal for each of the remote control buttons. The control system balances the robot during the climbing by separately adjusting the rotation speed of each DC motor proportional to the tilt angle of the robot frame. Pulse-width modulation technique was used to control the speed of DC motors. A two axes tilt sensor was used for concurrently measuring the tilt angle of the robot in both X and Y axes. A microcontroller ATmega64 was used to analyze the received data from the tilt sensor and the remote control and to generate an appropriate PWM signal for each DC motors. For programming, the microcontrollers were used in Bascome IDE interface in basic language. An electronic board was designed to connect the sensor, data receiver and motors to the microcontroller. The robot tested in field and maximum tilt angle was 8 and 6 degrees for Y and X axes, respectively.